On the Economics of Others - Oded Stark (Ekonomista, 2013)
We relate to others in two important ways: we care about others, and we care about how we fare in comparison to others. In some contexts, these two forms of relatedness interact. Caring about others can conveniently be labeled altruism. Caring about how we fare in comparison with others who fare better than ourselves can conveniently be labeled relative deprivation. I provide examples of domains in which the incorporation of altruism and relative deprivation can point to novel perspectives and suggest rethinking, and possibly revising, long-held views. And I show that there are domains in which consideration of relative deprivation can substitute for the prevalence of altruism, and vice versa. I conclude that this is a fascinating sphere for research on economics and social behavior.
Keywords: D01; D03; D13; D31; D63; D64; F22; F24; J61; O15; 330; Altruism; Relative deprivation; Economic and social behavior